Odwrócona pożyczka hipoteczna - nowoczesny instrument konwersji kapitału na rynku nieruchomości - Buszko, Michał (Reverse Mortgage - A Modern Instrument Of Equity Conversion In The Real Estate Market, 2008)
A reverse mortgage is one of the innovative financing method of individuals. Generally, this product is sold to low income old persons being homeowners. It enables them to convert part of the equity in their homes into tax-free cash inflows without selling real estate, giving up the title or taking on a new mortgage payment. The reverse mortgage allows upgrading the quality of life during the retirement and increasing the incomes of old people. It also helps to stay the homeowners in their homes and still meet their financial obligations. This financial instrument is linking the real estate market, deposit market, as well as life insurance market. Contrary to traditional mortgage loans the reverse mortgage defers the payback time to the period after the death of the individual. As the reverse mortgage is under research in Poland and it is expected to be introduced into the Polish market in the nearest future, this article presents main features, advantages and disadvantages of such financial instrument.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 84-91